Sustainable and Competitive Small Familiar Businesses (SFB). A Qualitative Approach to SFBs from Automotive Service Activity in Ciudad Juarez, Mexico - González Macías, Carlos Jesús (2019)
This paper analyzes the experienced reality by Small Familiar Businesses (SFB), aiming to determine the sustainable focus in the SFB owner’s decision-making process in relation to their type of vision. For this purpose, a literature review was conducted based on information obtained from different researches and data. A qualitative method was conducted through 10 in-depth interviews from SFB owners in Ciudad Juárez, Mexico. Findings show a will in SFBs to be competitive in order to be sustainable. The study’s research is relevant because it made possible to identify the sustainability and competitiveness factors through an explicative model for the SFB that may help them to develop an adequate decision-making process in order to achieve their success through time.